Construction of Tree Biomass Tables in Turkey for the Estimating of Biomass Potential for Energy - Saracoglu, N. (Taylor & Francis Inc, 2011)
According to economists and other observers of the energy scene, there is an impending shortage in the civilized world of petroleum and gas. Exhaustion of these nonrenewable fuels prompts consideration of alternative energy sources. One alternative source is forest biomass, which is defined as the quantity constituted by living organisms in the forest ecosystem in terms of mass. The aboveground portions of trees and shrubs transform solar energy in the form of vegetational substances. Because the forest is a renewable natural resource, plantations of trees and natural stands that were previously considered unmerchantable are now being examined as a new source of renewable energy. To help overcome a possible future energy shortage, methods of correctly managing and using forest biomass resources have to be developed now. The need for knowledge of the existing amount of standing timber and its growth in terms of mass, as measured and expressed by consistent methods and standars, is a part of this broad problem. The solution can be approached by producing biomass tables for tree species.
Keywords: Biomass Tables; Renewable Energy; Tree Species; Turkey